ECG changes and notable markers in ischemic stroke: a systematic review - Meitong Lin; Hongling Zhu (Heliyon)
Electrocardiography (ECG) changes have been linked with ischemic stroke (IS). However, conclusions on the association remains controversial. We summarized the research progress on the association between ECG changes and IS since 2000. 117 papers from 28 countries were included. Our results suggest that P-wave terminal force in V1 (PTFV1), atrial fibrillation (AF), interatrial block (IAB), premature atrial complexes (PAC) had salient association with the risk of IS. Notably, AF and IAB also had an evident association with cardioembolism stroke (CES). With regard to prognosis, prolonged QTc (PQTc) interval, T wave inversion and AF were intensely associated with mortality while corrected-QT dispersion (QTcd) was associated with poor functional status. According to similar pathological mechanisms in the atria, we infer that PTFV1, AF, IAB, PAC could be combined as “atrial markers in IS” to evaluate the risk of IS, especially CES for elderly people. PQTc interval, T wave inversion, AF and QTcd could be markers for prognosis evaluation. This systematic review could promote clinical use of ECG in IS and offer insights into researches on brain-heart axis by evaluating markers from various ECG parameters and arrythmias in IS.